2012
DOI: 10.3174/ajnr.a3298
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Intraindividual Comparison of Single-Dose Gadobenate Dimeglumine and Double-Dose Gadopentetate Dimeglumine for MR Angiography of the Supra-Aortic Arteries (the Supra-Aortic VALUE Study)

Abstract: BACKGROUND AND PURPOSE:Gadobenate dimeglumine has markedly higher R1 relaxivity compared to gadopentetate dimeglumine meaning that lower doses can be used to achieve similar contrast enhancement. Our aim was to prospectively compare single-dose gadobenate dimeglumine with double-dose gadopentetate dimeglumine for contrast-enhanced MRA of the supra-aortic vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…50 These findings in the supra-aortic arteries are supported by the findings of numerous intraindividual crossover studies in other vascular territories. [81][82][83][84][85][86] It is reasonable to conclude that increased GBCA concentration (as seen in Gadavist) and significant increases in r1-relaxivities (to the magnitude seen with MultiHance) would each be beneficial for increased vascular signal intensity for CE-MRA, though the benefit obtained from higher concentrations may be accompanied by a concomitant shortening of the optimal image-acquisition timing window when both agents are injected at similar rates.…”
Section: Contrast-enhanced Mr Angiographysupporting
confidence: 73%
See 1 more Smart Citation
“…50 These findings in the supra-aortic arteries are supported by the findings of numerous intraindividual crossover studies in other vascular territories. [81][82][83][84][85][86] It is reasonable to conclude that increased GBCA concentration (as seen in Gadavist) and significant increases in r1-relaxivities (to the magnitude seen with MultiHance) would each be beneficial for increased vascular signal intensity for CE-MRA, though the benefit obtained from higher concentrations may be accompanied by a concomitant shortening of the optimal image-acquisition timing window when both agents are injected at similar rates.…”
Section: Contrast-enhanced Mr Angiographysupporting
confidence: 73%
“…[49][50][51] In a very early study of 12 patients referred for CE-MRA of the carotid arteries, Pediconi et al 49 compared a single 0.1-mmol/kg dose of MultiHance with a double (0.2-mmol/kg) dose of Magnevist and found superior quantitative and qualitative enhancement with MultiHance for carotid time-resolved CE-MRA. Both doses of GBCAs were administered at a fixed rate of 2 mL/s, and the better imaging performance was ascribed to the higher r1 of MultiHance.…”
Section: Intraindividual Crossover Studies Comparing Gbcas For Ce-mramentioning
confidence: 99%
“…This increased r1 relaxivity translates into increased signal intensity enhancement relative to that achieved with conventional gadolinium agents at equivalent dose [4][5][6][7][8][9][10][11][12]. Previous studies have shown that a single 0.1 mmol/kg bodyweight dose of gadobenate dimeglumine can fully replace a double 0.2 mmol/kg body weight dose of gadopentetate dimeglumine for specific MR imaging applications, including CE-MRA [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have shown that a single Gd‐BOPTA dose can replace a double Gd‐DTPA dose for several MR applications. Gd‐BOPTA yielded qualitatively and quantitatively comparable diagnostic results compared with full‐dose Gd‐DTPA in several previous studies of the brain, heart, and vascular system …”
Section: Discussionmentioning
confidence: 94%